Abandoned agricultural land for renewable energy use: comparative analysis of Lithuania and Latvia - Tumelienė, Eglė; Sužiedelytė Visockienė, Jūratė; Gurskienė, Virginija; Malienė, Vida (International Conference “Environmental Engineering”, 2023)
The Abandoned Agricultural Land (AAL), which has been left overgrown with bushes, trees and invasive plants, has a negative impact on the environment and socio-economic development. As Lithuania and Latvia have a significant amount of AAL and a great demand for energy supply in autumn-spring periods, both countries have been chosen for analyses. The research aim was to assess the use of AAL for Renewable Energy (RE), such as Wind Energy (WE) and Solar Energy (SE). The dynamics of AAL in Lithuania and Latvia have been evaluated. The Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis has been applied to examine the AAL’s use for RE in both countries. The use of AAL for RE in both countries despite higher seasonality and low wind and solar potential, especially in territories where land abandonment is prevalent, may be a profitable option to combining these two types of RE or creating an energy mix along with other energy sources.